Electroencephalography in the Diagnosis of Genetic Generalized Epilepsy Syndromes - Seneviratne, Udaya; Cook, Mark J.; D’Souza, Wendyl Jude (Frontiers in Neurology, 2017)
Genetic generalized epilepsy (GGE) consists of several syndromes diagnosed and classified on the basis of clinical and electroencephalographic (EEG) features. The EEG signature of GGE is bisynchronous, symmetric and generalized spike-wave complex. Other typical EEG features include polyspikes, polyspike-wave discharges, occipital intermittent rhythmic delta activity, eye-closure sensitivity, fixation-off sensitivity and photoparoxysmal response. However, admixed with typical changes, atypical epileptiform discharges are also commonly seen in GGE. There are circadian variations of generalized epileptiform discharges. Activation procedures such as sleep, sleep deprivation, hyperventilation, intermittent photic stimulation, eye closure and fixation-off are useful techniques to increase the yield of EEG abnormalities. Specific triggers such as pattern stimulation and cognitive tasks are useful in eliciting reflex seizure-related EEG abnormalities in selected patients. Distinct electrographic abnormalities to help classification can be identified among different electroclinical syndromes.